2009
DOI: 10.1158/0008-5472.can-09-0758
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Transforming Growth Factor-β Receptor II Accelerates Prostate Tumorigenesis in the TRAMP Mouse Model

Abstract: The contribution of a dysfunctional transforming growth factor-B type II receptor (TGFBRII) to prostate cancer initiation and progression was investigated in an in vivo mouse model. Transgenic mice harboring the dominantnegative mutant TGF-B type II receptor (DNTGFBRII) in mouse epithelial cell were crossed with the TRAMP prostate cancer transgenic mouse to characterize the in vivo consequences of inactivated TGF-B signaling on prostate tumor initiation and progression. Histopathologic diagnosis of prostate sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…TGF-b1 functions as a paracrine growth inhibitor in normal cells of the epithelial lineage by inducing cell cycle arrest and apoptosis, and many human cancers escape from TGF-b1-mediated growth suppression by mutational alterations of its receptors or Smads (Markowitz et al, 1995). Unlikely normal epithelial cells, carcinoma cells produce active TGF-b1, which promotes tumor growth, migration and metastasis (Stearns et al, 1999;Zhu and Kyprianou, 2005;Lu et al, 2007;Pu et al, 2009). In prostate tumorigenesis, TGF-b1 has biphasic functions, having a growth inhibitory effect at early stages, but at later stages enhancing the malignant properties of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-b1 functions as a paracrine growth inhibitor in normal cells of the epithelial lineage by inducing cell cycle arrest and apoptosis, and many human cancers escape from TGF-b1-mediated growth suppression by mutational alterations of its receptors or Smads (Markowitz et al, 1995). Unlikely normal epithelial cells, carcinoma cells produce active TGF-b1, which promotes tumor growth, migration and metastasis (Stearns et al, 1999;Zhu and Kyprianou, 2005;Lu et al, 2007;Pu et al, 2009). In prostate tumorigenesis, TGF-b1 has biphasic functions, having a growth inhibitory effect at early stages, but at later stages enhancing the malignant properties of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, both intracellular and serum TGF-b1 levels are elevated in cancer patients and further increased in patients with metastatic carcinoma (Truong et al, 1993). Several studies have shown that prostate cancer cells are resistant to TGF-b1-induced growth inhibition, and TGF-b1 actually promotes tumor growth, migration and metastasis, indicating that TGF-b1 action is oncogenically conversed in the process of tumorigenesis (Stearns et al, 1999;Zhu and Kyprianou, 2005;Lu et al, 2007;Pu et al, 2009). We reported that TGF-b1 promotes cellular proliferation of prostate carcinomas through the activation of Ras/MAPK signaling and induction of tumor-promoting genes, such as interleukin-6, indicating that prostate cancers have a selective growth advantage by autocrine TGF-b1 production (Park et al, 2000(Park et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…20,23 The function of p53 and Rb is abrogated by SV-40 large T antigen; as a result, TRAMP male mice develop spontaneous progressive stages of PCa with time from early lesions of prostatic intraepithelial neoplasia (PIN) to late stage adenocarcinoma. 20,23 Furthermore, this PCa model has been also crossed with other genetically manipulated mice so as to generate bigenic mice, [28][29][30][31] which are employed to study the role of specific molecules in PCa progression. The changing patterns of CDKs and cyclins have been also well characterized during the progression of PCa in TRAMP model; 32 notably, we have reported the increased expression of p21 protein in TRAMP prostate with advanced stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Mutational inactivation of TGF-b signal-transduction components, such as the TGF-b type II receptor (TGFbRII) (60) or its mediators, Smad2 and Smad4, leads to defective TGF-b signaling in some cancers (17,59). Pu et al developed a transgenic adenocarcinoma of mouse prostate-based prostate cancer transgenic mouse model that harbors the dominant negative mutant TGF-b type II receptor in epithelial cells to characterize the in vivo consequences of inactivated TGF-b signaling on prostate tumor initiation and progression, and found that disruption of TGF-b signaling in vivo accelerated pathologic malignant changes in the prostate by altering the kinetics of prostate growth and inducing EMT (143). These findings indicate that TGF-b exerts its tumor suppressor functions through inhibition of cell proliferation, induction of apoptosis, and regulation of autophagy.…”
Section: Tumor Necrosis Factor-alphamentioning
confidence: 99%